2020
DOI: 10.1136/bmjopen-2019-034483
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perspectives of the new National Cervical Screening Program: a qualitative interview study of North Queensland women—‘I could be that one percent’

Abstract: ObjectivesTo investigate women’s understanding and attitudes towards the National Cervical Screening Program (NCSP) and to explore methods to improve screening participation.DesignSemi-structured face-to-face interviews were conducted through convenience and snowball sampling. Thematic analysis occurred using the interpretivist framework.SettingA private general practice in North Queensland.ParticipantsWomen between the ages of 18 and 74 who attended the general practice were eligible to participate. Fourteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…given the known concerns by screening-eligible women about the changes. 7,9 Before implementation, research reported that only 40-60% of clinicians found the main program changes acceptable. 12 Our study demonstrates increasing acceptance of the new guidelines, consistent with another recent survey of clinicians pre-and post-renewal which found that comfort in implementing the renewed program increased throughout the implementation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…given the known concerns by screening-eligible women about the changes. 7,9 Before implementation, research reported that only 40-60% of clinicians found the main program changes acceptable. 12 Our study demonstrates increasing acceptance of the new guidelines, consistent with another recent survey of clinicians pre-and post-renewal which found that comfort in implementing the renewed program increased throughout the implementation period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that women may be concerned about the extended screening interval and later starting age. [6][7][8][9] Healthcare provider endorsement increases patients' acceptance of screening program changes, 10,11 emphasising the importance of clinicians being able and willing to explain the changes to women and respond confidently to their concerns.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed increasing age, level of worry about developing cervical cancer, and having been previously screened impacted women’s feelings about the delayed screening start age and increased screening intervals. Older women’s previous screening experiences, family history and personal encounters with cervical cancer either themselves or through friends prior to the age of 25, may motivate these women to maintain regular screening practices 7,22 . Previous research highlights that women’s previous experience of receiving/not receiving screening was significantly associated with their attitude concerning screening 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This research provides timely information about the new NCSP. It is part of a mixed methods study and this allowed for a qualitative explanatory component, which has been separately published 11 . Additionally, a valid survey was developed using pre‐existing literature and expert advice, which was piloted within the target audience prior to distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Female patients between 18 and 74 years old were offered waiting room surveys by the receptionist over a 2‐month period. An explanatory qualitative component was simultaneously completed and is published separately 11 …”
Section: Methodsmentioning
confidence: 99%